Multiple stressors and the functional diversity of coastal ecosystems - (:unkn) unknown (My University, 2025)
Understanding how widespread changes to earth’s ecosystems will impact the many services that humankind derives from them is one of the greatest scientific problems today. The functional structure of multispecies assemblages is a critical determinant of how ecosystems control the flow of nutrients, matter and energy between trophic levels and ultimately how these flows feed back to the earth system trhough processes such as respiration or biomass accumulation. The functional diversity of multispecies assemblages is shaped by the different processes influencing local and regional patterns of species abundance and composition, both biotic and abiotic. Coastal regions worldwide are diverse and productive areas that have been impacted by humans since prehistory and are now threatened by the multiple stressors arising from global climate change and the sustained human exploitation of coastal resources. The arid western coast of South America is the most productive upwelling ecosystem of the planet and provides a rich record of coastal molluscs assemblages in the past, both fossilized or in the form of cultural deposits. These palaeontological and archaeological records have been intensively studied in some specific areas of coastal Northern Chile that lie close to areas where long-term ecological studies of rocky shore communities and their ecological dynamics have been carried out. We propose to leverage on this unique combination of information and expertise with the goals of establishing (i) how the functional diversity of coastal ecosystems has changed over a sequence of oceanographic and biotic events since the late Pleistocene, (ii) what is the current pattern of functional diversity along the coast of Chile, and (iii) how changes in fuctional diversity are translated to ecosystem functioning. To accomplish our goals and using our current understanding of ecological and oceanographic processes in the study region, we will test several hypotheses to address the nature of changes in functional diversity and how such changes can impact key aspects of ecosystem function, from local to regional scales. Our methods will be based on the analysis and synthesis of palaeontological, archaeological and ecological records of coastal biota, new dating and isotopic analyses, oceanographic monitoring and ecological field surveys and experiments. Firstly, we will draw on existing datasets, archived molluscan samples and publications available for Central-Northern Chile from late Pleistocene-early Holocene fossil and sub-fossil molluscan deposits in the area (22? -32?S) and prolonged occupational sequences from shell middens around Tal-tal (25?S). These publications, datasets and specimen collections, all leveraged through our interdisciplinary collaboration, hold a record of biodiversity changes through the Holocene and its analysis will allow us to establish the diversity, structure and changes in composition of a stable species pool across a broad geographic region. This approach will be complemented by a compilation of publicly-available datasets of artisanal fisheries landings to assess the spatial structure of mollusc production with oceanographic regime, which will be complemented through isotopic analysis of modern shells. Secondly, we will examine functional diversity by classifying each species using a comprehensive set of characteristics by recording multiple morphological parameters that can be assessed for all species from past and present assemblages and we will extend the multivariate trait space to include other functional characteristics, such as trophic status, mobility patterns and larval type. In the case of the extant assemblage, we will increase our insights into functional structure by studying dynamic ecological processes, such as local community composition at multiple sites and patterns of larval supply at sites located in contrasting oceanographic regimes. Finally, we will test the insights from changes in functional diversity through statistical modelling and field surveys by conducting a proof-of-concept manipulative field experiment. To this end, we will determine and use locations located in contrasting oceanographic contexts in the region to manipulate local functional diversity and establish how a key aspect of ecosystem functioning, biomass accumulation measured as ash-free dry weight, is impacted by changes in functional diversity under different oceanographic scenarios. The expected results of this multidisciplinary effort are ambitious, yet straightforward. By focusing on past and present evidence from a particular region and using its alongshore oceanographic patchiness we will establish large-scale, long-term variation of functional diversity in a coastal ecosystem and we will examine the consequences for ecosystem functioning under contrasting environmental settings. These results will also contribute to quantify the impacts of functional change on ecosystem functioning using field-based oceanographic settings measured through an ecosystem-level response variable. Our results aim to establish empirical patterns of change and test them experimentally, something that, to our knowledge, has never been attempted under such a comprehensive approach and using the wealth of data that we propose to bring together. Hence, by relying on a unique and robust multidisciplinary collaboration, we aim to understand the impacts of changes in functional diversity in the past and forecast how functional changes in coastal biodiversity will impact crucial ecosystem processes on one of the most productive coastal zones of the planet.